2013
DOI: 10.1371/journal.pone.0080098
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblast CFTR Inactivation Reduces Differentiation and Osteoprotegerin Expression in a Mouse Model of Cystic Fibrosis-Related Bone Disease

Abstract: Low bone mass and increased fracture risk are recognized complications of cystic fibrosis (CF). CF-related bone disease (CFBD) is characterized by uncoupled bone turnover—impaired osteoblastic bone formation and enhanced osteoclastic bone resorption. Intestinal malabsorption, vitamin D deficiency and inflammatory cytokines contribute to CFBD. However, epidemiological investigations and animal models also support a direct causal link between inactivation of skeletal cystic fibrosis transmembrane regulator (CFTR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 47 publications
2
37
0
4
Order By: Relevance
“…Cystic fibrosis patients carrying the common F508del mutation in the CFTR gene and mice carrying an inactivated CFTR allele suffer from bone mineralization defects leading to osteoporosis and osteopenia (37)(38)(39)(40). The mechanisms of how CFTR operates in osteoblasts are only poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Cystic fibrosis patients carrying the common F508del mutation in the CFTR gene and mice carrying an inactivated CFTR allele suffer from bone mineralization defects leading to osteoporosis and osteopenia (37)(38)(39)(40). The mechanisms of how CFTR operates in osteoblasts are only poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Of the identified 1,900 mutations of CFTR in humans, deletion of the phenylalanine at position 508 (DF508) is the most frequent mutation found in CF patients, which results in a folding defect and endoplasmic reticulum associated degradation of CFTR [17]. It is being recently recognized that apart from transporting anions, CFTR is involved in other cellular functions, including inflammation [6,18], proliferation [19][20][21], and differentiation [22][23][24] in bronchial epithelia, granulosa cells, enterocytes, and osteoblasts. Several signaling molecules associated with CFTR have been reported, including MAPK and NF-κB [6,18,[25][26][27][28].…”
mentioning
confidence: 99%
“…Mutation of the CFTR gene itself may have a direct role in the pathogenesis of CF-related bone disease (17). Some studies have indicated that the loss of CFTR activity in osteoblasts decreases the secretion of osteoprotegerin (OPG) resulting in accentuated inflammationdriven bone resorption (21). The evidence available about the use of bisphosphonates for osteoporosis in individuals with CF is limited.…”
Section: Cystic Fibrosismentioning
confidence: 99%